Adherence Pheno-genotypic of Escherichia coli O157:H7 Isolated from Beef, Feces of Cattle, Chicken and Human - I Wayan Suardana; Wayan Tunas Artama; Widya Asmara; Budi Setiadi Dayono (Indonesian Journal of Biotechnology, 2011)
Generally, adherence of micro-organisms to host cells is the frst step of the colonization to host surfaces.Escherichia coli O157:H7 can colonize to the intestine and induce attaching-effacing (AE) lessions. The capacityof inducing AE lesions is encoded by a pahtogenicity island, the locus of enterocyte effacement (LEE) thatcontains genes involved in generation of attaching and effaching (A/E) lesions. Among which that, the eaegene is encoding intimin, an outer membrane protein that is responsible to intimate attachment to the intestinalepithelial cells. A total of 20 local isolates obtained from human clinically, beef, cattle, chicken, and humannon-clinically were tested to adherence pheno-genotypic of E. coli O157:H7. The eae gene was identifed usingpolymerase chain reaction with a specifc primer i.e AE19 forward and AE20 reverse. To confrm phenotypicof gene, further study was performed by culturing the bacteria in vero cell, followed by Giemsa staining andAcridine Orange Fluorescent staining 3 h and 6 h after incubation, respectivelly. Result of study showed thatthere were 19 out of 20 (95%) isolates identifed positive eae gene. Giemsa staining appeared that the bacteriawith positive eae gene performed a cluster arroud of cell (localized adherence). On the other hand, the negativeeae gene appeared as a diffuse adherence (DA). The study indicated that almost all of E. coli O157:H7 localisolates which was positive eae gene had potency to colonize to the intestine and induce attching-effachinglessions, and also cause cytopahatic effects in intestinal epithelial cell